Quantum correlations in the two-photon decay of few-electron ions - Fratini, Filippo; Surzhykov, Andrey; Jahrsetz, Thorsten (Journal of physics. Conference Series, 2012)
The photon-photon polarization entanglement in the two-photon decay of metastable ionic states has been analyzed in the framework of the density matrix and second-order perturbation theory. Emphasis is placed especially upon the relativistic and non-dipole effects along the hydrogen- and helium-isoelectronic sequence.
Gesehen am 27.04.2018